Identification and Genetic Analysis of a Common Molecular Variant of Histidine-rich Glycoprotein with a Difference of 2KD in Apparent Molecular Weight - Hennis, B C; van Boheemen, P A; Wakabayashi, S; Koide, T; Hoffmann, J J M L; Klevit, P; Dooijewaard, G; Jansen, J G; Kluft, C (Thrombosis and Haemostasis, 1995)
Two forms of histidine-rich glycoprotein (HRG) were detected on SDS-PAGE by silver staining and immunoblotting after isolation of the protein from pooled plasma using immuno-affinity chromatography followed by chromatography with heparin-Sepharose. Both forms were single-chain molecules and the apparent molecular weights of form 1 and form 2 were 77 kD and 75 kD respectively. Mendelian inheritance of both HRG forms was observed in four families with 24 informative meioses, strongly suggesting that the two forms are encoded by different alleles. The frequency of form 1 and form 2 in a group of 36 individuals was 0.35 and 0.65 respectively.The difference between the two molecular variants was studied by direct sequence analysis of amplified exons of the HRG gene from 6 individuals who were homozygous either for form 1 or form 2. Five amino acid polymorphisms in three different exons were observed: Ile/Thr in exon 4; Pro/Ser in exon 5; His/Arg, Arg/Cys and Asn/Ile in exon 7. Analysis of these polymorphisms in 20 volunteers showed that only the Pro/Ser polymorphism at position 186 in exon 5 was coupled to the form of the HRG protein. Ser was found in form 1 and Pro in form 2. The presence of Ser at position 186 introduces a consensus sequence for a N-glycosylation site (Asn-X-Ser/Thr). By removing N-linked sugars with N-glycanase, it could be demonstrated that the difference between the two forms of HRG is caused by an extra carbohydrate group at Asn 184 in form 1.